Learning from picture books: Infants’ use of naming information - Khu, Melanie; Graham, Susan A.; Ganea, Patricia (Frontiers in Psychology, 2014)
The present study investigated whether naming would facilitate infants’ transfer of information from picture books to the real world. Eighteen- and 21-month-olds learned a novel label for a novel object depicted in a picture book. Infants then saw a second picture book in which an adult demonstrated how to elicit the object’s non-obvious property. Accompanying narration described the pictures using the object’s newly learnt label. Infants were subsequently tested with the real-world object depicted in the book, as well as a different-color exemplar. Infants’ performance on the test trials was compared with that of infants in a no label condition. When presented with the exact object depicted in the picture book, 21-month-olds were significantly more likely to attempt to elicit the object’s non-obvious property than were 18-month-olds. Learning the object’s label before learning about the object’s hidden property did not improve 18-month-olds’ performance. At 21-months, the number of infants in the label condition who attempted to elicit the real-world object’s non-obvious property was greater than would be predicted by chance, but the number of infants in the no label condition was not. Neither age group nor label condition predicted test performance for the different-color exemplar. The findings are discussed in relation to infants’ learning and transfer from picture books.